2021
DOI: 10.1097/ju.0000000000001941
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Prostate Cancer Progression in Active Surveillance Patients with Bilateral Disease Detected by Combined Magnetic Resonance Imaging-Fusion and Systematic Biopsy

Abstract: Purpose: We sought to evaluate whether bilateral prostate cancer detected at active surveillance (AS) enrollment is associated with progression to Grade Group (GG) 2 and to compare the efficacy of combined targeted biopsy plus systematic biopsy (Cbx) vs systematic biopsy (Sbx) or targeted biopsy alone to detect bilateral disease. Materials and Methods: A prospectively maintained database of patients referred to our institution from 2007e2020 was queried. The study cohort included all AS patients with GG1 on co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
(27 reference statements)
0
7
0
Order By: Relevance
“…The setting of this study in the contemporary era of MRF-TB increases the generalizability of the results, as MRI is increasingly used to improve the initial assessment of cancer grade. However, it is important to note that prostate MRI does not eliminate the possibility of misclassification [5] . In this context, we found that baseline clinical parameters—including PSA density, number of cores positive for cancer, MRI findings, and age—offered only marginal discriminative ability for prediction of biopsy upgrading but were improved by the addition of the Decipher classifier.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The setting of this study in the contemporary era of MRF-TB increases the generalizability of the results, as MRI is increasingly used to improve the initial assessment of cancer grade. However, it is important to note that prostate MRI does not eliminate the possibility of misclassification [5] . In this context, we found that baseline clinical parameters—including PSA density, number of cores positive for cancer, MRI findings, and age—offered only marginal discriminative ability for prediction of biopsy upgrading but were improved by the addition of the Decipher classifier.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from randomized trials and institutional cohort studies supports the long-term safety of active surveillance and its effectiveness as a strategy to avoid or defer definitive treatment [2] , [3] . Nonetheless, 20–60% of patients who are initially enrolled in active surveillance ultimately experience reclassification of their disease according to changes in biopsy Gleason grade, prostate-specific antigen (PSA) levels, or cancer volume [4] , [5] . As a result, up to half of patients undergo definitive treatment in the near term, most frequently because of Gleason upgrading [6] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of bilateral disease has also been shown to increase the risk of progression on AS (HR = 3.06; 95% CI = 1.31–7.13), and combined FB and SB improve detection of bilateral disease than either method alone. 38 …”
Section: Resultsmentioning
confidence: 99%
“…Surveillance Patients with Bilateral Disease Williams et al (page 1157) from Bethesda, Maryland retrospectively studied prediction of progression in patients on active surveillance and evaluated the impact of bilateral disease. 10 All patients had grade group I cancer on initial biopsy, and 41% with unilateral disease progressed on followup biopsy compared to 61% with bilateral disease. Progression was detected in 16% of patients with bilateral cancer using combined targeted plus systematic biopsies compared to targeted alone.…”
Section: Risk Of Prostate Cancer Progression In Activementioning
confidence: 94%